Nonergodic quadratic operators for a two-sex population - Ganikhodjaev, Nasir; Jamilov, Uygun; Mukhitdinov, Ramazan (Springer, 2014)
We describe the structure of quadratic operators of a two-sex population that differs from the model studied by Lyubich and give an example of nonergodic quadratic operator for a two-sex population.